Useful Victims: Symbolic Rage and Racist Violence on the Global Extreme-Right - Simon Purdue (Journal for Deradicalization, 2021)
The extreme-right has long relied on false claims of anti-White violence and racialized victimhood narratives in order to promote violence and advance their ideology. By carefully curating a ‘siege mentality’ among adherents, extremist writers and ‘philosophers’ have positioned whiteness as something under attack, and mobilized the ideas of demographic peril and endangered whiteness in order to justify rhetorical and physical violence against people of color and minority communities. This mythology has been a constant feature of the publications and propaganda of far-right groups around the world, and has been used to further the constructed image of extremist racist organizations as protectors of both whiteness and womanhood. This rhetoric has been used to radicalize individuals to the point at which they see violence as acceptable and necessary – an oft-repeated process which reached its most recent tragic conclusion in 2016 when a white man murdered 9 worshippers at the Emanuel African Methodist Episcopal Church in Charleston, South Carolina, saying to one victim; “you rape our women… you have to go”. This article analyzes the ways in which extremist right-wing groups in South Africa, the United Kingdom and United States have historically constructed the threat of anti-White violence and mobilized it in order to spread hate and radicalize individuals towards violent action. I argue that the extreme-right has consistently perpetuated a mythology surrounding race and sexuality in order to justify continued rhetorical and physical violence against communities of color, LGBTQ people, and the Jewish community.